Renewable Energy Consumption, Poverty Alleviation and Economic Growth Nexus in South Africa: ARDL Bounds Test Approach - Khobai, Hlalefang (International Journal of Energy Economics and Policy, 2021)
This study examines the relationship between renewable energy consumption, poverty alleviation and economic growth in South Africa. The paper applies the Autoregressive distributed lag (ARDL) model to examine the long run relationship and the Vector Error Correction Model (VECM) to determine the direction of causality between the variables. Quarterly data is used for the period 1990 – 2018. The findings of the paper established a presence of a long run relationship between renewable energy consumption, poverty, economic growth, financial development and government expenditure. Specifically, renewable energy consumption and economic growth have a negative and significant impact on poverty in both long run and short run. The VECM suggest that renewable energy consumption Granger-causes both economic growth and poverty in the long. Moreover, there is a bidirectional causality flowing between poverty and economic growth. The results have important implication for renewable energy policy makers as it can be realised that policies that promote adoption of clean technology will alleviate poverty in South Africa. Keywords: Renewable energy consumption, poverty alleviation, economic growth, South Africa JEL Classifications: C32, D04, Q47, Q42, Q01 DOI: https://doi.org/10.32479/ijeep.7215